2014
DOI: 10.1002/mnfr.201400550
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of LPS‐induced transcription and cytokine secretion by the dietary isothiocyanate sulforaphane

Abstract: Scope: Diets rich in cruciferous vegetables are associated with lower levels of pro-inflammatory cytokines, which may contribute to potential health-promoting properties of these vegetables. We investigate whether sulforaphane (SF), an isothiocyanate (ITC) obtained from broccoli, could suppress LPS-induced transcription and subsequent pro-inflammatory cytokine secretion at a physiologically relevant concentration using in vitro models of chronic inflammation. Methods and results:We find that exposure of the LP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 41 publications
(68 reference statements)
3
18
0
Order By: Relevance
“…A previous report showed that sulforaphane inhibited the secretion of IL‐6 from PBMC . In this study, sulforaphane also inhibited IL‐6 secretion from PBMC especially under stimulation by LPS (Figure A).…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…A previous report showed that sulforaphane inhibited the secretion of IL‐6 from PBMC . In this study, sulforaphane also inhibited IL‐6 secretion from PBMC especially under stimulation by LPS (Figure A).…”
Section: Resultssupporting
confidence: 76%
“…A previous report showed that sulforaphane inhibited the secretion of IL-6 from PBMC. 24 In this study, sulforaphane also inhibited IL-6 secretion from PBMC especially under stimulation by LPS ( Figure 6A). IL-6 mRNA expression in KF112 cells and the concentration of IL-6 protein in the supernatant were increased by the coculture with PBMC at 24 and 96 hours ( Figure 6B and C).…”
Section: The Effect Of Sulforaphane In a Coculture Model With Pbmcsupporting
confidence: 57%
See 1 more Smart Citation
“…This observation is in agreement with and confirms Marikovsky's and Batya's application to use thiram as a component of some pharmaceuticals useful as an anti-inflammatory agent 11 . In the literature, there are many proofs that compounds with pro-oxidative activity restrain inflammatory response in cells [67][68][69][70][71] . Such paradoxical effects are also known among antioxidants, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Koo et al, 2013 The suppression of signaling by covalent modification of cysteine residues 246 and 609 in human TLR4 Folkard et al, 2014 curcumin…”
mentioning
confidence: 99%